Combination lenvatinib plus pembrolizumab in the treatment of ovarian clear cell carcinoma: A case series - Corinne A. Calo; Monica D. Levine; Morgan D. Brown; David M. O'Malley; Floor J. Backes (Elsevier, 2023)
Effective second-line treatment options for patients with recurrent ovarian clear cell carcinoma (OCCC) are limited. This case series sought to report tumor characteristics and oncologic outcomes in a small group of patients treated with combination lenvatinib and pembrolizumab.A retrospective analysis of patients with ovarian clear cell carcinoma treated with combination lenvatinib and pembrolizumab at a single institution was performed. Patient and tumor characteristics were collected including demographics and germline/somatic testing. Clinical outcomes were also evaluated and reported.Three patients with recurrent OCCC were included in the study. The median age of patients was 48 years old. All patients had platinum-resistant disease and had received 1-3 prior lines of therapy. The overall response rate was 100% (3/3). Progression-free survival ranged from 10 months to not-yet-reached. One patient remains on treatment, while the other two died of disease with overall survival of 14 and 27 months.Combination lenvatinib-pembrolizumab demonstrated favorable clinical response in these patients with platinum-resistant, recurrent, ovarian clear cell carcinoma.